31=2y-5
Add 5 on both -5+5 which cancels out and 31+5 which is 36 and then divide 36 by 2 which equals to 18.
So y=18 hope this helped (':
Equation 1: y = -2x + 1
Equation 2: y = 2x - 3
Since both equations already have y isolated, we are able to simply set the right side of both equations equal to each other. Since we know that the value of y must be the same, we can do this.
-2x + 1 = 2x - 3
1 = 4x - 3
4 = 4x
x = 1
Then, we need to plug our value of x back into either of the original two equations and solve for y. I will be plugging x back into equation 2 above.
y = 2x - 3
y = 2(1) - 3
y = 2 - 3
y = -1
Hope this helps!! :)
Step-by-step explanation:
x² + y² − 8x + 10y − 8 = 0
Rearrange:
x² − 8x + y² + 10y = 8
To complete the square, take half of the x and y coefficients, square it, then add the result to both sides.
(-8/2)² = 16
(10/2)² = 25
x² − 8x + 16 + y² + 10y + 25 = 8 + 16 + 25
x² − 8x + 16 + y² + 10y + 25 = 49
Factor the squares:
(x − 4)² + (y + 5)² = 49
The center is (4, -5) and the radius is 7.
If you add 7 and 6 you get 13 witch would be 1 ten plus 5 tens equals 6 tens and 3ones